Pilot Survey of Female Anesthesiologists' Childbearing and Parental Leave Experiences. Issue 1 (March 2020) - Pearson, A.C.S.; Dodd, S.E.; Kraus, M.B.; Ondecko Ligda, K.M.; Hertzberg, L.B.; Patel, P.V.; Chandrabose, R.K.
Abstract : ( Anesth Analg . 2019;128(6):e109–e112) Because of the fact that recovery from childbirth is a crucial period in a woman's life, experts in a number of medical communities have issued policy statements on parental leave and breastfeeding accommodations for physicians. However, the American Society of Anesthesiologists (ASA) has not put forth any guidelines on either parental leave or breastfeeding arrangements. Previous research has been conducted to study how female surgeons' careers are affected by childbearing, but there are no studies that examine how parental leave and breastfeeding would influence an anesthesiologist's professional career. The aim of this study was to record information on women working in anesthesiology to understand their impressions on pregnancy, childbirth, recovery from childbirth, and lactation in the context of their career.